PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI INSTALASI FARMASI RUMAH SAKIT UMUM SRIWIJAYA PALEMBANG - Erina Aslamia; Mukran Roni (Universitas Bina Taruna Gorontalo, 2024)
This study aims to examine the influence of the work environment, work discipline and employee performance. The method used is quantitative, the object of research is employees at the Pharmacy Installation of the Sriwijaya General Hospital Palembang. The sampling technique was carried out in total sampling with a sample size of 36 respondents, collecting data using a questionnaire. The data analysis technique was carried out using SmartPLS 4. The results of this study indicate that first, the work environment has a significant effect on employee performance (H1 Accepted). Second, work discipline has a significant effect on employee performance (H2 Accepted). From the results of this study it is hoped that further research can discuss more in-depth factors such as employee loyalty, job satisfaction and work commitment.